Bulk Passivation and Interfacial Passivation for Perovskite Solar Cells: Which One is More Effective?. Issue 9 (6th March 2021) - Wang, Jintao; Jin, Guangyong; Zhen, Qingzhu; He, Chenyang; Duan, Yu
Abstract: Perovskite solar cells (PSCs) have emerged as promising candidates for photovoltaic applications because of their superior optoelectronic properties. The power conversion efficiency of 25.5% has been achieved at an astonishing speed from the debut of 3.8%. However, the notoriously poor stability stemming from the solution fabrication process and uncontrollable rapid crystallization limits the commercialization of PSCs. Thus defects are inevitable among the bulk films and interfaces. Herein, recent progress about defects passivation by additive strategy among the bulk film, are discussed. More importantly, the defects passivation strategy for perovskite/electron transport layer and perovskite/hole transport layer interfaces are summarized. Furthermore, how defects passivation and ion migration would affect the stability performance of the perovskite devices are elaborated. Finally, the current challenges for commercialization prospects of perovskite photovoltaic applications are discussed. Abstract : In this article, the recent achievements on defects passivation for perovskite solar cells (PSCs) are summarized. Especially, the bottom interfacial passivation strategies for high‐performance PSCs are emphasized. At the same time, the effects of ion migration to the stability of perovskite device are summed up. Finally, the current challenges for the commercialization of perovskite devices are discussed.